Dr. Seuss' how the Grinch stole Christmas - Price, Jeffrey; Seaman, Peter S.; Grazer, Brian, 1953-; Howard, Ron, 1954-; Carrey, Jim, 1962-; Tambor, Jeffrey, 1944-; Baranski, Christine; Shannon, Molly, 1964-; Momsen, Taylor; Irwin, Bill, 1950-; Howard, Clint, 1959-; Hopkins, Anthony, 1937-; et al. (Universal City, Calif. : Universal, 2001)
Why is the Grinch such a grouch? No one seems to know, until little Cindy Lou Who takes matters into her own hands and turns both Whoville and the Grinch's world upside down, inside out, and funny side up in her search for the true meaning of Christmas.
Special features: Anamorphic widescreen (1.85:1) -- The Grinch: Spotlight on location ; deleted scenes ; outtakes ; Who school ; Makeup application and design ; Seussian set decroation ; Visual effects ; Faith Hill "Where are you Christmas?" music viceo ; Wholiday recipes ; By the numbers ; Theatrical trailer ; The Grinch's special offer ; Production notes ; Cast and filmmakers ; Grinch game ; DVS (descriptive video service) -- Max's Playhouse: Sing-along songs ; Read-along "The care and feeding of a Grinch" ; Dress the Grinch ; Rhyme time -- Language: English 5.1 surround ; English DTS 5.1 surround ; French 5.1 surround -- Captioned: English -- DVD-ROM features.
Based on the book by Dr. Seuss.
Special features include deleted scenes, outtakes, spotlight on location, Max's Playhouse, music video.
Closed captioned for the hearing impaired.
Director of photography, Donald Peterman ; editors, Daniel P. Hanley, Mike Hill ; music composed by James Horner ; narrator, Anthony Hopkins.
Jim Carrey, Jeffrey Tambor, Christine Baranski, Molly Shannon, Taylor Momsen, Bill Irwin, Clint Howard.
MPAA rating: PG.
Keywords: Grinch (Fictitious character) -- Drama